The impact of organizational variables on job stress among teachers in Sabah / Najihah Hanisah Marmaya - Marmaya, Najihah Hanisah (2008)
Over the past years, numerous researches in the West have been conducted seeking to establish a relationship between organizational variables and job stress. Despite the strong indication that job stress issues are an increasingly important phenomenon in Asian countries, studies on job stress are still limited in Malaysia. The study of stress among teachers in Malaysia have been 'done quite extensively and brought about tremendous development in management and job stress field. 'The study on job stress among teachers in Sabah has yet to be conducted actively. 'The present study examined the impact of organizational variables on job stress among teachers in Tawau and Lahad Datu Sabah. The organizational variables are role conflict, work overload and teaching facilities. A sample size of 177 teachers from Tawau and Lahad Datu participated in this study. The result revealed that teachers in Tawau and Lahad Datu experienced low stress levels. This study also found that there is a positive relationship between organizational variables and job stress. It also indicates that the higher the